Faktor-Faktor Yang Mempengaruhi Keputusan Non Muslim Menjadi Anggota Pada KSPPS Fastabiq Khoiru Ummah Pati - Hana, Kharis Fadlullah (IAIN Kudus, 2018)
The purpose of this study was to find out what factors influence the decision of non-Muslims to become members of the Savings and Loans Cooperative (KSPPS) Fastabiq Khoiru Ummah Pati. Cooperatives are joint business entities that move to improve the welfare of their members based on sharia principles. The sharia cooperative is a new instrument in financial institutions in Indonesia, but its development has experienced a very significant increase. From the data of the Indonesian Central Bureau of Statistics, it was stated that there were 498 business entities in the form of sharia cooperatives spread across various provinces throughout Indonesia. This is influenced by the high interest of the community to become members of both Muslim and non-Muslim circles. The situation is interesting to note that cooperatives based on Islamic sharia principles are also in demand among non-Muslims. Innovative services, promotions and products that are in accordance with the daily needs of the community are the things that most influence their decisions.